Influência do relevo e de diferentes usos sob atributos físicohídrico em latossolo - Panziera, André Gonçalves (2016)
Soil is an important means of supplying water to meet the need for agricultural management systems. It is its physical-water properties that make it capable of regulating the availability of water. This study evaluates how the relief forms and different uses influence some physical-water properties of a Red Latosol on a slope in the Rio Grande do Sul Plateau region, and what the implications of these attributes may be on soil water dynamics. In one part of the experimental area with herbaceous cultivation without agricultural traffic, and in another with the no-tillage system, with crops rotation of wheat, soybean and oat, as well as, the use of machinery on the soil. Ten representative sites of the study area were selected as experimental units. In these experimental units, a trench of 0.9 m depth, 1.5 m length and 1.0 m width was excavated. Three depths 30, 60 and 90 cm were delimited for each experimental unit. At each depth, 5 samples of soil with non-deformed structure were collected, being 15 per experimental unit and 150 throughout the study area. All profiles were morphologically examined to characterize the structure, consistency, color, amount of roots, pore type, horizons and soil spots. Physical analyzes of soil density, total porosity, texture and saturated hydraulic conductivity were performed. Levels contours were generated from a topographic planialtimetric survey. In the computational program, it generated preferential arrows of surface runoff and slope interval. It was characterized, for each experimental unit, the forms of slopes. It was found that, in general, in the study area, the curvature in the profile and plane were convergent concave, respectively. Based on this information, the flow of the area tends to converge to a single region, with flows influenced by declivity ranging from 1.83% to 20% in the area as a whole. In the area under no-tillage system, as a function of the saturated hydraulic conductivity, the vertical movement of the water, when it reached depths of 60 cm, was observed. The clay texture was preponderant to 90 cm depth, indicating distribution of the pore size that leads tortuosity of the preferred water paths for storage. Hydrologically, the Latosol under study contains physical characteristics that imply the generation of sub-superficial lateral flow. The flow pattern is governed up to 30 cm deep by angle variations and position of the slope, controlling the soil's ability to conduct water, infiltrate the profile, and transport sediments. The high percentage of clay is the main factor governing the Dynamics of water in 60 and 90 cm, be attributed to the nature of the soil.